2018
DOI: 10.1097/hjh.0000000000001749
|View full text |Cite
|
Sign up to set email alerts
|

Changes in albuminuria and renal outcome in patients with type 2 diabetes and hypertension

Abstract: In patients with hypertension and T2D under real-life clinical conditions, changes in albuminuria parallel changes of renal risk. Albuminuria status could be a guide to optimize therapeutic strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…In general, the results of such studies support those of the major outcomes trials, even though in most countries, SGLT2 inhibitors are not prescribed in patients with eGFR < 60 mL/min/1.73 m 2 , limiting the possibility to extend these observations to a T2D population at higher renal risk. In people with T2D and hypertension, changes in albuminuria occurred in parallel with changes in adverse renal outcomes in an observational study [ 104 ], and other studies have shown that UACR is a strong predictor of albuminuria progression in people with T2D [ 105 ]. Baseline prevalence of microalbuminuria and macroalbuminuria in EMPA-REG OUTCOME (28.7% and 11%, respectively) [ 30 ] and the CANVAS program (23% and 8%, respectively) [ 106 ] were also similar to that reported in real-world studies [ 105 , 107 ].…”
Section: Renoprotective Effects Of Sglt2 Inhibitors According To Basementioning
confidence: 99%
“…In general, the results of such studies support those of the major outcomes trials, even though in most countries, SGLT2 inhibitors are not prescribed in patients with eGFR < 60 mL/min/1.73 m 2 , limiting the possibility to extend these observations to a T2D population at higher renal risk. In people with T2D and hypertension, changes in albuminuria occurred in parallel with changes in adverse renal outcomes in an observational study [ 104 ], and other studies have shown that UACR is a strong predictor of albuminuria progression in people with T2D [ 105 ]. Baseline prevalence of microalbuminuria and macroalbuminuria in EMPA-REG OUTCOME (28.7% and 11%, respectively) [ 30 ] and the CANVAS program (23% and 8%, respectively) [ 106 ] were also similar to that reported in real-world studies [ 105 , 107 ].…”
Section: Renoprotective Effects Of Sglt2 Inhibitors According To Basementioning
confidence: 99%
“…Albuminuria is a known marker of renal damage and has been shown to have a strong cardiovascular and renal predictive power. Furthermore, modifications of urinary albumin excretion under pharmacological treatment might impact CV and renal prognosis independent of blood pressure reduction [ 9 11 ]. In the classical, five-stage course of diabetic nephropathy, mostly derived from studies conducted in patients with type 1 diabetes, microalbuminuria has traditionally been taken to represent the first sign of renal involvement [ 12 ] (Fig.…”
Section: Antihypertensive Treatment and Renal Protection In Type 2 DImentioning
confidence: 99%
“…Another recent European population-based study showed that BP control was not achieved among most hypertensive patients with diabetes mellitus and the mean BP was 142 /81 mm Hg. 26 Studies have shown that any decrease in albuminuria was strongly related to decreased risk for CV events and all-cause mortality as well as improved renal outcomes . 1012 Over the study period, the prevalence of albuminuria decreased by nearly 20% (from 39.1% to 31.3%, P = .02).…”
Section: Discussionmentioning
confidence: 99%